The development of an interactive e-worksheet using wizer.me on social studies learning for grade 7 at junior high school - Driya Safina Sahida; Agung Wiradimadja (JINoP (Jurnal Inovasi Pembelajaran), 2024)
In the learning process, obstacles are often found such as students having difficulty understanding the material, boredom while studying, and a lack of motivation to learn. This results in the learning process being less than optimal. Based on pre-research activities at SMPN 3 Krian, Sidoarjo District. Based on pre-research activities at SMPN 3 Krian, Sidoarjo, the learning process in class did not use teaching materials in the form of the electronic worksheet so students had difficulty understanding the material and were bored during the learning process This research aims to develop an interactive e-worksheet based on wizer.me to overcome these problems. This research method is Research & Development using the ADDIE model with analysis, design, development, implementation, and evaluation steps. As the result of this research, the author succeeded in developing an interactive e-worksheet based on wizer.me which involves students with e-worksheet in the learning process. students will not only see and hear but there will be interaction or reciprocity between students and the e-worksheet. This interactive e-worksheet can help students understand the material and increase learning motivation. Based on the research results, this e-worksheet is very feasible and can be used in social studies learning so that it can help students understand the subject matter.